Pengaruh Struktur Kepemilikan Terhadap Konservatisme Akuntansi - Nazilah Nazilah; Syaiful Syaiful (Universitas Muhammadiyah Gresik, 2023)
This study aims to examine the effect of ownership structure (institutional, managerial and public) on accounting conservatism. This study uses quantitative research. The data analysis technique used multiple linear regression analysis with SPSS version 25.0. The data used in this research is documentary data in the form of financial reports. Variable Accounting conservatism is measured using the accrual measure, institutional ownership is measured by the percentage ratio of the number of institutional shares to the number of shares outstanding by the company. Managerial ownership is measured by the percentage ratio of the number of managers' shares to the number of shares outstanding by the company. Public ownership is measured by the percentage ratio of the number of shares owned by the general public to the number of shares issued by the company. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2020. Sampling was carried out using a purposive sampling method with a total sample of 76 data. The results of this study indicate that the variable institutional ownership structure and managerial ownership structure have no effect on accounting conservatism. Meanwhile, the public ownership structure variable has a significant negative effect on accounting conservatism.